Circulaciones culturales de danzas afro urbanas. Redes, representaciones étnico-raciales desde Guadalajara (México) - Aidaluz Sánchez Arismendi (Nuevo mundo - Mundos Nuevos, 2025)
The Ivorian coupé-décalé, the Congolese ndombolo, the Angolan kuduro and the Ghanaian azonto, among other musical-dance styles have been grouped in certain contexts as Afro-modern, Afro or Afro-urban dances. These styles have been widely disseminated among the youth of different latitudes and ethnic-racial identities, through music videos, social networks and dance classes, both virtual and face-to-face. In Guadalajara, Mexico, a network of practice has emerged that connects local dancers with other practitioners from diverse African and European backgrounds, showing a network of learning and circulation, often mediated by virtuality. The article focuses on the identification and analysis of practice networks mainly among residents of Guadalajara and Mexico City. It examines forms of circulation and recreation of ethno-racial representations in a context where the national perception of the black and Afro-descendant is situated as something foreign. Based on interviews with dancers (teachers and students), mostly autoidentified as mestizos, and through participant observation of classes and festivals in Guadalajara (2021-2022), the article identifies the interconnection between "afro" dance circuits, the importance of authenticity and the simultaneity between the questioning of stereotypes and their persistence.